Revisiting Happiness and Well-Being in Later Life from Interdisciplinary Age-Studies Perspectives - Ieva Stončikaitė (Behavioral Sciences, 2019)
Important demographic shifts and the so-called ‘longevity revolution’ have generated profound transformations in social interpretations of old age, an increased interest in age studies and new ideas on how to age well. The majority of current successful ageing models, however, represent rather a prevailing construct in Western societies. Physical and psychosocial well-being and the ability to adjust to the ideals of successful ageing are often seen as an integral part of a good quality in life. Those who do not or cannot follow these lines are often regarded as morally irresponsible and seem to be doomed to have a lonely, unhealthy and unhappy later life. This paper questions the current discourses of successful ageing in terms of healthy and happy living and calls for a reconsideration of more global, integrated and holistic understandings of the process of growing old.